2022
DOI: 10.3390/ijms23052781
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Amide Hydrolase (FAAH) Inhibition Plays a Key Role in Counteracting Acute Lung Injury

Abstract: Acute lung injury (ALI) is a group of lung illnesses characterized by severe inflammation, with no treatment. The fatty acid amide hydrolase (FAAH) enzyme is an integral membrane protein responsible for the hydrolysis of the main endocannabinoids, such as anandamide (AEA). In pre-clinical pain and inflammation models, increasing the endogenous levels of AEA and other bioactive fatty acid amides (FAAs) via genetic deletion or the pharmacological inhibition of FAAH produces many analgesic benefits in several dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 110 publications
1
6
0
Order By: Relevance
“…Radice and colleagues demonstrated that vinclozolin was able to induce lipid peroxidation in the Hep92 cell line [ 28 ]. As previously proven in other cell types, we found a significant increase in DNA damage, verified by the activation of PARP, a well-known marker of DNA damage, as well as an increase in lipid peroxidation, proven via an MDA level investigation [ 29 , 30 , 31 , 32 , 33 , 34 ]. Different studies demonstrated that vinclozolin administration induces granulosa cell apoptosis during follicular atresia in pigs, as well as apoptosis in testis [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 79%
“…Radice and colleagues demonstrated that vinclozolin was able to induce lipid peroxidation in the Hep92 cell line [ 28 ]. As previously proven in other cell types, we found a significant increase in DNA damage, verified by the activation of PARP, a well-known marker of DNA damage, as well as an increase in lipid peroxidation, proven via an MDA level investigation [ 29 , 30 , 31 , 32 , 33 , 34 ]. Different studies demonstrated that vinclozolin administration induces granulosa cell apoptosis during follicular atresia in pigs, as well as apoptosis in testis [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 79%
“…Fatty acid amide hydrolase (FAAH) is a transmembrane protein responsible for the hydrolysis of the endocannabinoid N-arachidonoylethanolamide (AEA) and other related amidated signaling lipids, such as N-oleoylethanolamide (OEA), linoleoylethanolamide (LEA), and palmitoylethanolamide (PEA) [ 148 ]. Inhibition of FAAH exhibits a protective role in the development of ALI by suppressing the activation of NF-κB pathway as well as the expression of pro-inflammatory cytokines in a dose-dependent manner [ 149 ]. N-acylethanolamine acid amidase (NAAA) is a cysteine hydrolase generally expressed in immune cells, which is also responsible for the hydrolysis of FAEs.…”
Section: The Impact Of Free Fatty Acids and Its Derivatives On Alimentioning
confidence: 99%
“…(IV) Sham groups+URB878: animals received URB878 dissolved in a vehicle for 14 days at the dose of 5 mg/kg. Doses were chosen based on a work carried out in our lab in an experimental model of carrageenan-induced acute lung injury [52].…”
Section: Experimental Design and Groupsmentioning
confidence: 99%